A new species of Blakea (Melastomataceae: Blakeeae) with pendulous flowers from Costa Rica - Michelangeli, Fabián A.; Santamaría-Aguilar, Daniel (Phytotaxa, 2020)
We describe Blakea ricardoi (Melastomataceae: Blakeeae), a species known only from the Parque Internacional La Amistad in Costa Rica side.  It can be distinguished by the long peduncles up to 6.5 cm long, pendant flowers with green petals and indumentum of roughened trichomes. A key to other species of Blakea with pendulous flowers and connivent petals is provided.